Corpus callosum agenesis and rehabilitative treatment - Chiappedi Matteo; Bejor Maurizio (BMC, 2010)
Abstract Corpus callosum agenesis is a relatively common brain malformation. It can be isolated or included in a complex alteration of brain (or sometimes even whole body) morphology. It has been associated with a number of neuropsychiatric disorders, from subtle neuropsychological deficits to Pervasive Developmental Disorders. Etiology and pathogenetic mechanisms have been better understood in recent years, due to the availability of more adequate animal models and the relevant progresses in developmental neurosciences. These recent findings are reviewed (through a MedLine search including papers published in the last 5 years and most relevant previously published papers) in view of the potential impact on children's global functioning and on the possible rehabilitative treatment, with an emphasis on the possibility to exploit brain plasticity and on the use of the ICF-CY framework.